2015
DOI: 10.1016/j.geoforum.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

The financial entanglements of local energy projects

Abstract: a b s t r a c tThere is currently an expansion of local energy initiatives, underpinned by the desire to reduce energyrelated carbon emissions and in recognition of the importance of the local arena to achieving such change. Much of the research on these initiatives has been framed by a conventional economic approach, identifying barriers, drivers and incentives to explain their emergence (or not). Here a new economic sociological approach is taken which sees markets as socio-materially constructed and points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Private sector actors, such as energy utilities, developers, and independent consultants, have a complex and powerful influence on community and local energy projects (Rydin et al, ), and there are important considerations to make about the extent to which market actors and market‐based rationalities shape the ways in which community energy is conceived, mobilised, and enacted.…”
Section: The Private Sectormentioning
confidence: 99%
“…Private sector actors, such as energy utilities, developers, and independent consultants, have a complex and powerful influence on community and local energy projects (Rydin et al, ), and there are important considerations to make about the extent to which market actors and market‐based rationalities shape the ways in which community energy is conceived, mobilised, and enacted.…”
Section: The Private Sectormentioning
confidence: 99%
“…We ascertain that economic studies specifically focused on the economic and financial viability of community energy projects [15,[24][25][26][27][28][29][30][31][32]. Most attention to local and community energy was in the subfields of energy economics and ecological economics.…”
Section: Theoretical Approaches Of Community Energymentioning
confidence: 99%
“…It has been suggested that the structuring of such initiatives has a history going back to a time before the rise of climate energy issues (Nadaï et al 2015) and relies on processes that weave together multiple dimensions (spatial, material, socio-institutional, political, market, etc.) in rather singular and contingent ways (Rydin 2014). In-depth longitudinal case studies are useful in understanding both the processes of emergence of local initiatives, the re-articulation between policy support and market, and how we (and governments) might learn from them in a period in which these initiatives are becoming numerous, a process of learning that might not start from or through the transfer of solutions or outcomes as if they were generic recipes.…”
Section: Exploring Entanglements and Temporalitiesmentioning
confidence: 99%
“…They first show in great detail how these entanglements are developed as these "local" initiatives emerge. The multi-dimensional and multi-scalar character of these entanglements has been pointed out in the literature (Rydin 2014), but this has mainly been adduced as a feature of local initiatives and in a static perspective. The case studies gathered here provide a new perspective as they follow the making of these entanglements in time and space, allowing for a critical perspective on the intersection between market and political engagement at work.…”
Section: Exploring Entanglements and Temporalitiesmentioning
confidence: 99%